Human capital and regional disparities: Advancing accounting frameworks with education, health, and population dynamics - Shuning Chen; Xiangdan Piao; Jun Xie; Shunsuke Managi (PLoS ONE, 2025)
This study advances the inclusive wealth accounting of human capital (HC) to improve global research on the valuation of HC for sustainability. By innovatively integrating complex population dynamics, including schooling and labor force participation, and using a net present value (NPV) valuation method aligned with capital budgeting principles, we quantitatively measure HC in 165 countries. As a methodological advancement, we use a unified framework that incorporates education, health and economic participation via the measurement of life expectancy in different life stages to inform sustainable development investments. Our analysis from 1990 to 2020 reveals significant differences in HC development across countries. While education is strongly correlated with GDP growth, disparities in health and economic participation are critical barriers to long-term HC accumulation. Our findings argue for a comprehensive policy approach that goes beyond investing in education for its financial benefits and includes substantial improvements in health and economic opportunities to promote more equitable HC growth. We emphasize the need to incorporate complex population dynamics into HC assessments to better understand and strengthen the interdependencies between these critical factors, with the aim of reducing global development gaps.